L’utilité de la formation dans la prévention des risques psychosociaux au travailprévention des risques psychosociaux, santé au travail, formation, ressources psychosociales - Sabrina Rouat (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article contributes to our knowledge about interventions in occupational health and safety. In this study, we asked how training in psycho-social risk prevention can help in the development of new psycho-social resources in organizations. The results are based on the analysis of 14 action plans and compare the degree of the psycho-social resources provided according to whether or not the actors had received PSR training before the primary prevention initiatives. The results analysis showed that, paradoxically, training tended to focus the actors’ initiatives on individual rather than on collective responses.